The Confines of Subjectivity: Spaces of Resistance in George Orwell’s Nineteen Eighty-Four - Tereszewski, Marcin (Nordic Journal of English Studies, 2019)
George Orwell’s Nineteen Eighty-Four, despite the vast political changes during the last half-century since its publication and its various aesthetic shortcomings, remains one of the most important and relevant books of this century. With the proliferation of modern post-apocalyptic and dystopian fantasies in both literature and film, it would be worthwhile to address the modernist visions of the future as they were formulated in architectural terms. The dystopian world described in the novel is brought into existence not only through the political and ideological relations to its cultural context but also by means of the spatial dimensions in which the dystopia is played out. The aim of this essay is, therefore, to identify the spatial framework along with the ideological context on the basis of which this project is defined in relation to the socio-political environment of Oceania in Nineteen Eighty-Four. It will be the underlying assumption of this article, drawing on Martin Heidegger’s notion of “dwelling” and modernist architectural theory, that the construction of space directly affects subjectivity and the creation of a sense of self, especially insofar as memory and history are concerned. This assumption will be developed with regards to Mr. Charrington’s antique shop representing here a space of resistance against the manifestations of modernist ideology.